2008
DOI: 10.1093/hmg/ddn249
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum quality control: a new mechanism of E-cadherin regulation and its implication in cancer

Abstract: E-cadherin is critical for the maintenance of tissue architecture and is a major component of adherens junctions. Its role in tumour development is well established, with many human carcinomas exhibiting E-cadherin loss at the invasive front. In many invasive carcinomas, the mechanisms leading to the loss of E-cadherin remains elusive. Here, we hypothesize that mechanisms of protein quality control play a key role in E-cadherin regulation. As a cell model system, we used CHO cells stably expressing E-cadherin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 22 publications
8
70
0
Order By: Relevance
“…14 Using functional in vitro assays, we demonstrated that cells expressing pathogenic CDH1 missense mutations fail to aggregate and become more invasive, in comparison with cells expressing wild-type (WT) E-cadherin, 5,12,[15][16][17][18][19][20][21][22] supporting their pathogenic relevance.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…14 Using functional in vitro assays, we demonstrated that cells expressing pathogenic CDH1 missense mutations fail to aggregate and become more invasive, in comparison with cells expressing wild-type (WT) E-cadherin, 5,12,[15][16][17][18][19][20][21][22] supporting their pathogenic relevance.…”
Section: Introductionmentioning
confidence: 85%
“…E-cadherin mutants T340A, A634V, R749W, E757K, E781D, P799R and V832M found in the HDGC context, 16,18,19,21,[34][35][36][37][38] were constructed by site-directed mutagenesis in the entry vector CDH1pENTR 221 (Clone ID: IOH46767, Invitrogen, Grand Island, NY, USA), following the protocol described by Wang and Wilkinson. 41 By LR recombination reaction, the open reading frame was subcloned in the pEF6/Myc-His vector (Invitrogen).…”
Section: Plasmids Constructionmentioning
confidence: 99%
See 3 more Smart Citations